Integrated upgrading of waste cooking oil–derived biodiesel via reaction pathway selection, adsorption, and feedstock blending - Misri Gozan; Mochamad Yusuf Efendi; Andre Fahriz Perdana Harahap; Anusith Thanapimmetha; Maythee Saisriyoot; Pattarawit Krajomethong; Penjit Srinophakun (Center of Biomass & Renewable Energy (CBIORE), 2026)
Biodiesel production from waste cooking oil (WCO) offers environmental and economic advantages but is constrained by degraded feedstock quality and unstable fuel properties. This study evaluates an integrated upgrading strategy combining reaction pathway selection, adsorption-based purification, and feedstock blending to produce fuel-grade biodiesel. WCO was pretreated by moisture removal and acid esterification using H₂SO₄ to reduce free fatty acids. Transesterification was conducted in a temperature-controlled batch reactor at 60 °C using 6:1–12:1 methanol-to-oil mass ratios, 1.0–2.0 wt% KOH catalyst loadings, and 60–120 minute reaction times. The maximum FAME content achieved was 93.94 wt% at 6:1 methanol ratio, 1.5 wt% KOH, and 90 min reaction time. Post-reaction upgrading was performed via batch adsorption using activated carbon (0.5–2 wt%, 60 °C) and silica gel (3 wt%, 112 °C). Adsorption improved FAME content to 94–95 wt% (maximum 95.3 wt% with silica gel) and reduced acid value and carbon residue. However, oxidation stability decreased slightly after adsorption (from 4.20 to 4.05 h), indicating partial removal of natural antioxidants. GC–MS analysis confirmed the dominance of methyl esters and the reduction of minor impurity-related peaks after purification. To comply with multi-parameter fuel requirements, WCO was blended with palm olein prior to conversion at ratios of 100:0 to 10:90 (w/w). Full EN 14214 compliance (FAME ≥ 96.5 wt%) was achieved at ≥50% palm olein, with oxidation stability of 10.2 h at a 10:90 ratio. These findings demonstrate that adsorption enhances compositional purity, whereas feedstock blending is decisive for restoring oxidative stability and achieving robust, fuel-grade biodiesel.